The advertisement call of Boana freicanecae (Carnaval & Peixoto, 2004) (Anura: Hylidae), an endemic and poorly known treefrog from northeastern Brazil - Marinho, Pedro; Roberto, Igor Joventino; Lisboa, Barnagleison S. (Zootaxa, 2020)
Boana freicanecae is a medium-sized hylid (males SVL= 37.3–42.2 mm) belonging to the B. pulchella group (Carnaval & Peixoto 2004). This species is associated with streams in Atlantic montane forests (450–750 m elevation) located from the Pernambuco Biogeographic Sub-Region (Silva & Casteleti 2003), in the states of Pernambuco and Alagoas, northeastern Brazil (Carnaval & Peixoto 2004; Cardoso et al. 2006). Currently, B. freicanecae is classified as ‘Data Deficient’ according to the Brazilian Red List of Threatened species (ICMBio 2018) and many aspects of its natural history (e.g., advertisement call) are poorly known. Here we describe the advertisement call of this treefrog based on calls obtained from two populations.